2016
DOI: 10.3354/aei00199
|View full text |Cite
|
Sign up to set email alerts
|

Erodibility of aquaculture waste from different bottom substrates

Abstract: A laboratory study was carried out to examine the effect of bed sediment texture on the erodibility of salmon aquaculture waste fecal material and salmon feed pellets. Erodibility measurements of this material were made using a Gust microcosm erosion chamber and artificially composed substrates of mud, sand, sand and gravel, sand and cobble, and cobble. Results show that cumulative mass eroded (CME) and erodibility constant (M) can vary by up to an order of magnitude depending on substrate composition, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 30 publications
2
25
1
Order By: Relevance
“…Although, DREAM takes into consideration seabed erosion and resuspension, the composition and type of sediment matters (Law et al, 2016). Refining the description of these processes is a point of potential improvement.…”
Section: Simulated and Observed Mud Thicknessmentioning
confidence: 99%
“…Although, DREAM takes into consideration seabed erosion and resuspension, the composition and type of sediment matters (Law et al, 2016). Refining the description of these processes is a point of potential improvement.…”
Section: Simulated and Observed Mud Thicknessmentioning
confidence: 99%
“…The hypothesis of sand resuspension during passage of the two storms can be reconciled with observed variations in the backscatter ratio, which was lower during passage of the two storms than it was during the period of spring tides. Permeable sand beds can store organic matter in the interstitial pore spaces [52]. We propose that during resuspension events, this organic material was resuspended, which caused backscatter ratios to decrease.…”
Section: Inferences From Optical Propertiesmentioning
confidence: 90%
“…The results of Law et al (2016) stress the need to include substrate-dependent sets of τ c values in existing particle-tracking models in order to simulate the spread of fish farming particle wastes more accurately. However, we see certain limitations in their study, such as the use of broken-down faecal material in the experiments, as well as turbidity measurements as indicators for particle resuspension, whereas video surveys have shown that most faecal material sits on the seabed as unbroken faeces (hereafter faecal pellets) with particle sizes on the order of several millimeters to a few centimeters (Bannister et al 2016).…”
Section: Introductionmentioning
confidence: 94%
“…A recent study by Law et al (2016) identified differences in τ c for feed pellets and faecal material using a Gust Microcosm Erosion Chamber (GMEC) and 5 different bottom substrates, concluding that substrate texture plays a major role in the resuspension of fishfarming wastes. Law et al (2016) calculated a single τ c of approximately 0.01 Pa for incipient motion of the faecal material, and substrate-dependent τ c for feed pellets ranging from 0.03 to 0.28 Pa for bottom material ranging from consolidated muds to cobbles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation